2020
DOI: 10.9755/ejfa.2020.v32.i2.2074
|View full text |Cite
|
Sign up to set email alerts
|

Fat substitution by inulin in goat milk ice cream produced with cajá (Spondias mombin) pulp and probiotic cultures: influence on composition, texture, and acceptability among consumers of two Brazilian regions

Abstract: The production of a goat milk ice cream with a typical Brazilian fruit, probiotic cultures and with the fat substitution by inulin could be an opportunity of products’ diversification for the growing goat dairy sector in Brazil and also to attend the consumers’ demand of healthy indulgence products. However, the probiotic stability and texture could be affected by the fat replacement in a frozen product, and sensory acceptability can vary according to the country region. The objective of this study was to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Açu, et al [ 42 ] also observed that these synbiotic ice creams maintained their probiotic properties during storage and had good sensory scores. de Paula et al [ 48 ] manufactured goat milk ice creams with Lactobacillus rhamnosus or Lactobacillus paracasei as probiotic cultures, and these microorganisms had high viability levels during storage. The added probiotics maintained viability levels above 8 Log CFU/g during storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Açu, et al [ 42 ] also observed that these synbiotic ice creams maintained their probiotic properties during storage and had good sensory scores. de Paula et al [ 48 ] manufactured goat milk ice creams with Lactobacillus rhamnosus or Lactobacillus paracasei as probiotic cultures, and these microorganisms had high viability levels during storage. The added probiotics maintained viability levels above 8 Log CFU/g during storage.…”
Section: Resultsmentioning
confidence: 99%
“…The production of ovine’s and caprine’s yoghurts and frozen yoghurts has also followed this trend. Several research works refer to the use of ewe’s [ 32 , 33 , 34 , 35 , 36 , 37 ] and goat’s [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] milks in the production of ice creams with functional properties. In addition, several authors reported the potential medicinal properties of small ruminant’s milks and dairy products [ 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…S. mombin has high levels of carotenoids, phenolic compounds, and antioxidant activity. However, when it comes to its by-product, there are few studies assessing its phenolic compounds profile [ 8 , 28 , 29 , 30 ]. Bataglion et al [ 29 ] evaluated the phenolic composition of S. mombin pulp and found a high gallic acid content (577.03 µg/g DWP), a compound that has antimicrobial and anti-carcinogenic activity in addition to a cardiovascular and neurological protective effect [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Passion fruit flavour has been used to mask the goaty flavour in ice cream which was more acceptable than hog plum and bacuri fruit (Macedo et al ., 2014). The use of 5% inulin as a fat replacer successfully substituted goat milk cream in ice cream formulation with improved sensorial attributes (de Paula et al ., 2020). Goat milk ice cream prepared using chocolate flavour at 10% fat content had the highest acceptability as compared to cow milk ice cream (Carvalho et al ., 2022).…”
Section: Technological Challenges and Strategies To Overcome Problems...mentioning
confidence: 99%